PERLINDUNGAN HUKUM PENGETAHUAN TRADISIONAL DALAM KONSEP HUKUM KEKAYAAN INTELEKTUAL - Muthia Septarina (Al-Adl, 2016)
As for the objectives of this study are to find out who is the subject of law which became the holder of the rights in the protect of traditional knowledge and to find out how the forms of legal protection granted to traditional knowledge this research is expected to provide a significant contribution both theoritycally and practically.This study uses research methods of socio-logical research using an interdisciplinary approach among aspects of social logical research using noemaive approach who used the method of qualitative analysis is by analyzing the data in depth and holistic as stated by David M Fettermen “this description might include the groups’s history, religion, politics, economy and environment” with another word presented the relationship between context in which is law located it is o meet the need for more detailed and thorough explaination of the legal issues in a more meaning full by making comparisons between law in book with law in action.